Bilateral multiple cavernous haemangiomas of the orbit. - Sullivan, T J (1992)
Orbital cavernous haemangioma, a common orbital tumour, is usually single and unilateral. We report the first case of histologically confirmed bilateral multiple cavernous haemangiomas of the orbit.